Eu & ela repensando gênero”: um estudo com perpetradores(as) de violência de gênero internos(as) do Sistema Prisional do Maranhão - Gomes, Loyane Ellen Silva (2024)
Violence is an event of great magnitude, considering that as it invades the life of one, in some way, it can affect the lives of everyone. However, it is certain that the frequency of this phenomenon should not be taken for granted or considered as a consequence of social interactions. The present study arose from the need and importance of understanding more about gender-based violence, especially from the perspective of those who perpetrate it. This is a multi-method study, with an emphasis on the qualitative approach, anchored in participatory research. The general objective of this study was to analyze the repercussions of the application of the project “Eu&Ela: Repensando Gênero” on the prevention and confrontation of gender violence among inmates of the prison system of São Luís/MA, Imperatriz/MA and Santa Inês/MA. The research participants were perpetrators of gender-based violence, with and without conviction, held in the prison system of the State of Maranhão under the application of Maria da Penha Law nº. 11.340/2006 and Articles 129 and 217/A of the Brazilian Penal Code. The Project is developed by the Public Defender's Office of the State of Maranhão (DPE/MA), in partnership with the State Secretariat for Penitentiary Administration (SEAP/MA) and with agreements with the National Secretariat of Penal Policies (SENAPPEN) and the National Secretariat of Justice (SENAJUS). To collect information, an instrument was used consisting of a Sociodemographic Questionnaire, legal processes present in the Unified Electronic Execution System (SEEU) and the Penitentiary Intelligence, Information and Prison Security System (SIISP) and, finally, semi-annual reports and Project Workshops. The study's Information Analysis is composed of sociodemographic data, organized through descriptive analysis and originating from documentary analysis carried out with the instruments mentioned above. Such processes make up the quantitative approach stage of the present study. The qualitative stage of Information Analysis was prepared based on Thematic Analysis (Minayo, 2014; Minayo; Deslandes; Gomes, 2016) carried out during the nine Workshops that make up the Project. The results found indicate that males are the ones who mostly perpetrate gender-based violence, specifically through crimes against the victims' sexual dignity, such as, for example, through rape, which totaled 47 legal cases in the State of Maranhão, followed by 15 cases of femicide identified in the prison system of São Luís - MA. On the other hand, the female gender, in the childhood phase, was identified as the most violated by gender-based violence in the state of Maranhão and had a kinship link with the perpetrator, with the main victims being those who were daughters, followed by stepdaughters and nieces. Furthermore, it was identified that the intra-family context is the most common scenario for more prolonged crimes, which involve more than two years of repeated sexual violence. The Workshops analyzed pointed out that, with regard to the perception of committed gender violence, the study elucidated that in the face of sexual crimes, there is a displacement on the part of the perpetrators of the responsibility they have, which is attributed only through the punitive dimension of the Maria Law da Penha no. 11,340/2006. In the categories that emerged from the Thematic Analysis, it was noted that resocialization is closely linked to extramurals, especially through family relationships, which can function as a resource for prospecting life in the prison system. Furthermore, state charges were a category present in the face of the need for actions to curb gender-based violence by the perpetrators of the phenomenon themselves, once again, a shift in responsibility was perceived. Furthermore, it was observed that the Project is a space to understand the perception that perpetrators have about gender violence and, therefore, this same data also works as a method of preventing the phenomenon. It is concluded, based on the results achieved in this study, that what was found encourages the continuity and replication of the “Eu&Ela: Repensando Gênero” Project, understanding that the Project proved to be a significant social equipment for curbing gender-based violence . Likewise, the implementation of the Project appears as a way of achieving the pedagogical and preventive dimensions of Law Maria da Penha nº. 11,340/2006, given that the prison system only uses the punitive dimension.